A unique method for management of benign colonic masses: case report - De, Anushtup; Nandi, Bhaskar; Bajwa, Jaspreet Singh; Singh, Rajesh K.; Parwan, Deepika; Dager, Poonam; Solanki, Chandraketu (International Surgery Journal, 2021)
Even though lipomas are most common non-epithelial tumors of the large intestine, they mostly present with non-specific symptoms. Intussusception is the most common morbidity related to such lesions and may present as intestinal obstruction. We present here a case of a young female who presented to gastroenterology department as a case of pain abdomen and nausea and a provisional diagnosis of subacute intestinal obstruction was kept. Contrast enhanced CT confirmed a diagnosis of intussusception due to an ascending colon mass? likely lipoma. The colonoscopy was done and biopsy was taken which was non-specific for malignancy. Patient, after taking due consent, was taken for surgery and laparoscopic assisted submucosal excision of lipoma was done and we will discuss the same. Endoscopic excision of lipomas has been reported but when failed, mostly segmental resection of the colon has been reported. To the best of our knowledge, this is the second reported case of laparoscopic assisted colotomy with submucosal excision of an intussuscepting colonic lipoma and first one in ascending colon.